Sense and Learn: Recent Advances in Wearable Sensing and Machine Learning for Blood Glucose Monitoring and Trend-Detection - Alhaddad, Ahmad Yaser; Aly, Hussein; Gad, Hoda; Al-Ali, Abdulaziz; Sadasivuni, Kishor Kumar; Cabibihan, John-John; Malik, Rayaz A. (Frontiers in Bioengineering and Biotechnology, 2022)
Graphical Abstract